2018
DOI: 10.1016/j.ultsonch.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic soldering of Cu alloy using Ni-foam/Sn composite interlayer

Abstract: In this study, Cu alloy joints were fabricated with a Ni-foam reinforced Sn-based composite solder with the assistance of ultrasonic vibration. Effects of ultrasonic soldering time on the microstructure and mechanical properties of Cu/Ni-Sn/Cu joints were investigated. Results showed that exceptional metallurgic bonding could be acquired with the assistance of ultrasonic vibration using a self-developed Ni-foam/Sn composite solder. For joint soldered for 5 s, a (Cu,Ni)Sn intermetallic compound (IMC) layer was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, reducing Ag also leads to the decrease of mechanical properties, including resistance to thermal fatigue and creep [100,101]. Different alloying elements have been added to improve the mechanical properties, including Ni, Bi, Zn, Sb, and Ga [102][103][104][105][106] and it has been found that small levels of additions can suppress the formation of large Ag 3 Sn plates in SAC solders, and improve the microstructure and mechanical properties [32]. For example, small Zn additions (e.g., 1.5 wt%) to a Sn-2.0Ag-0.7Cu solder refined Ag 3 Sn and Cu 6 Sn 5 particles, and also promoted the formation of small (Cu, Ag) 5 Zn 8 intermetallic particles, which improved the yield strength and ultimate tensile strength, at the cost of decreased ductility [107], as shown in Figure 12.…”
Section: Improved Service Reliability Of Soldersmentioning
confidence: 99%
“…However, reducing Ag also leads to the decrease of mechanical properties, including resistance to thermal fatigue and creep [100,101]. Different alloying elements have been added to improve the mechanical properties, including Ni, Bi, Zn, Sb, and Ga [102][103][104][105][106] and it has been found that small levels of additions can suppress the formation of large Ag 3 Sn plates in SAC solders, and improve the microstructure and mechanical properties [32]. For example, small Zn additions (e.g., 1.5 wt%) to a Sn-2.0Ag-0.7Cu solder refined Ag 3 Sn and Cu 6 Sn 5 particles, and also promoted the formation of small (Cu, Ag) 5 Zn 8 intermetallic particles, which improved the yield strength and ultimate tensile strength, at the cost of decreased ductility [107], as shown in Figure 12.…”
Section: Improved Service Reliability Of Soldersmentioning
confidence: 99%
“…Additionally, the reaction rate with various Ni particle amounts is obviously different, which has been shown to be an efficient grain refiner for boosting the shear strength of the Cu-Sn wafer bonding joints [19] , [20] , [21] . Hence, high strength and high melting-point Cu joints can be achieved in a short time by ultrasonic assisted soldering [11] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Open-cell Ni foam, which exhibits high strength and toughness and good metallurgical reactivity with Sn-based solder, has been considered as a promising strengthening phase to Snbased solders. In our previous study [15], Ni foam reinforced Sn-based composite solder was used to bond Cu substrates with an ultrasonic-assisted soldering method. Interfacial reactants, including (Ni,Cu) 3 Sn 4 and (Cu,Ni) 6 Sn 5 intermetallic compounds (IMCs), were formed in large quantity, homogeneously dispersed in the solder seam, and excellent bonding strength was obtained with the combined strengthening effects of the Ni skeletons and these IMC particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ultrasonic bonding technology is known to be unable to connect devices which require high precision and which are made from materials with brittle characteristics. The strength of Ni foam/Sn composite solder bonded Cu joints is largely correlated with the number and morphology of the Sn/Ni interfacial reaction phases [15]. When the soldering process is performed without the assistance of ultrasonic vibration, dense interfacial IMC layers are formed on the solid substrate surface [16,17], which may inhibit the interfacial reaction and thus deteriorate the strengthening effects of the metal foams.…”
Section: Introductionmentioning
confidence: 99%